Effect of guar gum and glycerol on oil absorption and qualities of banana chips - Sumonsiri, N. (2023)
The application of hydrocolloid as an edible coating can reduce oil absorption in fried products, leading to foods with lower oil content for consumers who are concerned about their health. The main purpose of the present work was to investigate the effect of guar gum and glycerol coating on oil absorption, physical properties, and sensory acceptance of fried banana chips. The results revealed that guar gum (1.00% w/w) and glycerol (5.66% w/w) coating provided the lowest oil content of fried banana chips (with 33.02% oil reduction as compared to the uncoated sample, and 15.19% oil reduction as compared to the sample coated with guar gum alone); highest fracturability and hardness with a slight change in colour, and acceptable sensory characteristics.